Gigantometopus coronobtectus sp. nov., the first Isometopinae (Hemiptera: Cimicomorpha: Miridae) from Vietnam - Kim, Junggon; Taszakowski, Artur; Herczek, Aleksander; Jung, Sunghoon (Zootaxa, 2021)
The new isometopine Gigantometopus coronobtectus sp. nov. from Vietnam is described and illustrated. A revised diagnosis of Gigantometopus and detailed information on nymphal morphology based on the last-instar nymph and description of the female genitalia are presented. A key to the species of the genus is provided and the position of G. schuhi is discussed based on the morphology of pronotum and scutellum.